Developing Video-Based English Textbook for Elementary School Students - Monika Widyastuti Surtikanti (Journal of English Language Teaching and Islamic Integration, 2019)
In the Curriculum 2013, English is excluded from the Elementary School Subjects,  especially  for  the  State  Elementary  Schools.  Some  private  elementary schools keep teaching English to their students. One of them is SD Kristen Widya Wacana  Jamsaren.  The  English  teachers  found  difficulty  in  providing  a  textbook that covers the students’ need. This is a Research and Development (R & D) study which conducts the preliminary survey, designing and developing the prototype of the  product,  conducting  limited  testing  and  product  validation,  having  a  revision process and describing the research result. This study  is aimed at finding out the students’ need and providing a video-based textbook to teach English for the sixth grade students of SD Kristen Widya Wacana Jamsaren. The video-based textbook is  developed  based  on  the  need  analysis,  syllabus  and  some  theories  related  to teaching English to young learners.